KONSTRUKSI IKON, INDEK, DAN SIMBOL DALAM MEMBANGUN VISUALISASI KARAKTER VIDEO GAME HARVEST MOON BACK TO NATURE - Budiman, Arief; Anwar, Ardy Aprilian (Jurnal Bahasa Rupa, 2020)
The presence of character visualization becomes part of the aesthetic value in video games, with its presence making events in the video game become interwoven and have a narrative flow. In the end it creates a fantasy as well as the occurrence of increasing emotion in playing video games, where players are expected to feel an understanding of indigo - value. Seeing the magnitude of the role of the presence of character visualization in video games. Then through the study of reading visual signs, it is done as a means to find out the sign construction on character visualization in the Harvest Moon Back to Nature video game. Descriptive Interpretative research methods using the semiotics approach with qualitative data analysis as an instrument to describe and interpret the object of study. Researchers use the Peirce semiotic approach as a signatory analysis theory can read visual signs in the form of icons, indices, and symbols contained in the visualization of characters oriented to aspects of the story in the Harvest Moon Back to Nature video games. Overall the existence of character visualization presented by the construction of visual signs (icons, indices, symbols) in the Harvest Moon Back to Nature video game has been able to describe the characteristics of each character in the game world that suits the personality and profession of the character played in the the Harvest Moon Back to Nature video game.